A Post-Lockdown Assessment of Albendazole Treatment Coverage in Mass Drug Administration Campaigns Implemented Before and During COVID-19 Pandemic in Ekiti, Southwest Nigeria - Mogaji, Hammed O.; Okoh, Hilary I.; Lawal, Abiodun M.; Ojo, Kayode H.; Marcus, Ayodele J.; Aaron, Nwana O.; Adeleye, Damilola R.; Olamiju, Francisca O.; Ekpo, Uwem F. (International Journal of Public Health, 2023)
Objective: This study assessed the coverage of albendazole (ALB) in mass drug administration (MDA) programs implemented before (2019) and during the (2020 and 2021) COVID-19 pandemic in Ekiti State, Nigeria. Methods: Standardized questionnaires were administered to 1,127 children across three peri-urban communities to ascertain if they received and swallowed ALB across the years. Reasons, why ALB was not received, were documented and analyzed in SPSS. 20.0. Results: In 2019, the medicine reach was between 42.2-57.8%, however, during the pandemic, the reach significantly reduced to 12.3-18.6%, and increased to 28.5-35.2% in 2021 (p<0.000). About 19.6-27.2% of the participants have missed 1 MDA, while 26.9-37.8% and 22.4 -32.8% have missed 2 and 3 MDAs, respectively. The majority who did not receive ALB (60.8-75%) claimed drug distributors never came, while about 14.9-20.3% mentioned they did not hear about MDA. However, individual compliance towards swallowing was above 94% across the study years (p<0.00). Conclusion: These results highlight the need to explore the perceptions of those who have consistently missed MDAs, and also understand the health-system-related issues including those imposed by the pandemic affecting MDA.